2016
DOI: 10.1007/s10040-016-1366-2
|View full text |Cite
|
Sign up to set email alerts
|

The use of salinity contrast for density difference compensation to improve the thermal recovery efficiency in high-temperature aquifer thermal energy storage systems

Abstract: The efficiency of heat recovery in high-temperature (>60°C) aquifer thermal energy storage (HT-ATES) systems is limited due to the buoyancy of the injected hot water. This study investigates the potential to improve the efficiency through compensation of the density difference by increased salinity of the injected hot water for a single injection-recovery well scheme. The proposed method was tested through numerical modeling with SEAWATv4, considering seasonal HT-ATES with four consecutive injection-storage-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 36 publications
4
17
0
Order By: Relevance
“…13), in contrast with the simulations with the highest ambient groundwater flow (50 m/y). Also the A/V ratios calculated for earlier simulation studies and experiments without ambient groundwater flow (Caljé, 2010;Doughty et al, 1982;Lopik et al, 2016) strongly correlate with the observed efficiencies in these studies. Like in this study, the results from Lopik et al (2016) and Doughty et al (1982) consist of a series systematic changing boundary conditions which allows for verification of the relations found in Fig.…”
Section: Contribution Of Conduction and Dispersion Lossessupporting
confidence: 57%
See 4 more Smart Citations
“…13), in contrast with the simulations with the highest ambient groundwater flow (50 m/y). Also the A/V ratios calculated for earlier simulation studies and experiments without ambient groundwater flow (Caljé, 2010;Doughty et al, 1982;Lopik et al, 2016) strongly correlate with the observed efficiencies in these studies. Like in this study, the results from Lopik et al (2016) and Doughty et al (1982) consist of a series systematic changing boundary conditions which allows for verification of the relations found in Fig.…”
Section: Contribution Of Conduction and Dispersion Lossessupporting
confidence: 57%
“…13. Results of both Lopik et al (2016) and Doughty et al (1982) show a linear relation with similar slope between the surface area over Fig. 10.…”
Section: Contribution Of Conduction and Dispersion Lossesmentioning
confidence: 66%
See 3 more Smart Citations